On the ordering of probability forecasts - Walter Krämer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2002)
The paper explores the relationship between various orderings among probability forecasts that have been suggested in the literature. It is shown that well calibrated forecasters are in general not comparable according to the domination ordering suggested by Vardeman and Meeden (1983), that the orderings based on ROC-curves and Gini-curves are identical, and that the domination ordering in conjunction with semicalibration implies the rest.
Keywords: 519; probability forecasts; calibration; refinement; domination